2018
DOI: 10.3390/insects9020040
|View full text |Cite
|
Sign up to set email alerts
|

Don’t Know Much about Bumblebees?—A Study about Secondary School Students’ Knowledge and Attitude Shows Educational Demand

Abstract: Many insects are threatened with extinction, which in the case of pollinating insects could lead to declining pollination services and reduced ecosystem biodiversity. This necessitates rethinking how we deal with nature in general. Schools are ideal places in which to instill a willingness to behave in an environmentally-friendly way. Whereas scientific studies and school textbooks stress the importance of honeybees as pollinators, the role of bumblebees is either underestimated or neglected. The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
(101 reference statements)
1
12
0
Order By: Relevance
“…Pests, fertilizers, and lack of good quality seeds were reported as the main pressing problems leading to decline in agriculture production. The level of education or type of crops grown did not seem to play a role in pollination awareness as reported by other studies [61][62][63]. The few farmers aware of pollinators seemed to have acquired this information from agriculture training programs or from other farmers.…”
Section: Pollinators Awarenessmentioning
confidence: 53%
“…Pests, fertilizers, and lack of good quality seeds were reported as the main pressing problems leading to decline in agriculture production. The level of education or type of crops grown did not seem to play a role in pollination awareness as reported by other studies [61][62][63]. The few farmers aware of pollinators seemed to have acquired this information from agriculture training programs or from other farmers.…”
Section: Pollinators Awarenessmentioning
confidence: 53%
“…gardens, allotments and spaces where they work or volunteer) and their perceptions drive the management of public spaces, which collectively span large and ubiquitous areas with a substantial capacity to support pollinators (Baldock et al., 2019). In recent years, there have been many public campaigns and newspaper articles about pollinators (see Appendix S1), and available evidence from Europe and North America suggests that people have reasonable levels of knowledge about, and generally positive attitudes towards, them (Schönfelder & Bogner, 2017; Sieg et al., 2018; Silva & Minor, 2017; Wignall et al., 2019). For example, a European public consultation with 67,000 responses showed that most respondents considered themselves to be well informed about pollinators, found pollinator declines alarming and felt significantly affected by pollinator declines (European Commission, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a European public consultation with 67,000 responses showed that most respondents considered themselves to be well informed about pollinators, found pollinator declines alarming and felt significantly affected by pollinator declines (European Commission, 2018). Furthermore, studies show that attitudes towards pollinators are positively related to knowledge and benefit from education (Bhattacharyya et al., 2017; Penn et al., 2018; Schönfelder & Bogner, 2018; Sieg et al., 2018; Silva & Minor, 2017; Toomey & Domroese, 2013). There is some indication that this knowledge is matched by an intention to protect pollinators, for example participants in a UK study were willing to pay an average of £43/household/year (£842 million/year nationally) for a policy to protect bees (Mwebaze et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This may be surprising as typically the general public views invertebrates, particularly arthropods, with fear and disgust (Kellert, 1993). However, Sieg, Teibtner, and Dreesmann (2018) found that although general knowledge of bumblebees amongst German secondary students was relatively low, their attitudes were generally positive. O'Hara (2012) found that both the majority of residents of a neighborhood in Guelph, Ontario and participants in gardening and pollinator‐themed organizations in that same city felt that there were no (63% and 61%) or only slight (37% for both) threats from bees, and that bees were extremely (83% and 77%) or very important (10% and 17%) to humans, respectively.…”
Section: Resultsmentioning
confidence: 99%